Influência do contato interproximal em próteses parciais fixas suportadas por implantes com conexão tipo cone Morse - Gil, Renata Rezende (2011)
Due to the difficulty of cleaning and comfort for the patient, some authors suggest that multiple adjacent implants are rehabilitated separately. The aim of this study was to evaluate the influence of the contact point in the success of adjacent implants compared with prosthetic rehabilitation on implants joined Morse taper. Photoelastic models were fabricated three implants with three Morse Taper 4.0 x 13.0 mm set straight, 2mm below the top edge of the model, straight line, varying the contact between the crowns and separated into 03 groups: Point Contact (PC) 1 mm diameter; Contact Surface (CS) 3mm diameter; splinted (ES), which was adapted fixed partial prostheses cemented Then the models were subjected to different types of loads: a = axial group (20N); b = lateral angle of 40° (20N) in the implant corresponding to the first molar, c = central axial (20N) in the implant corresponding to the second premolar. We obtained 30 images of each type of loading group (n = 30) in a circular polariscope. The values of fringe orders and maximum shear stress (τ) were obtained by the program Fringes by photoelastic analysis of 27 points in each image. We performed the Student t test with p <0.05 and calculate the area of graphics. The loads and lateral group had similar statistics gathering for the three groups (ES, PC, SC). In loading the central PC and ES groups had similar statistics, but were different statistically from the SC. Considering a general analysis, the ES group showed the best results for the stresses in the photoelastic model. Therefore, within the limitations of this study can conclude that splinting the crowns on multiple adjacent implants provided better biomechanical behavior for all types of loading. Groups PC, SC were the most susceptible to overload in the presence of side loading.